Understanding how individual, family and societal influences impact on Indigenous women’s health and wellbeing - Eades, Anne-Marie (2017)
Introduction This PhD study explores issues of stress, psychosocial health and chronic disease (CD) affecting Indigenous Australian women. It seeks to understand the impact of the roles and responsibilities Indigenous women have in their families and communities on their ability to manage their own health. Background In relation to the social determinants of health, Indigenous Australian women are the most socially and economically disadvantaged women in Australia. They face considerable disparity in relation to their health and wellbeing compared to other women in Australia. Indigenous Australian women are predominantly the sole care providers for close family members and are called upon to support family and community members through extended kinship networks. These women often experience limited educational and employment opportunities as a consequence. Women with such limited opportunities often face a lifelong trajectory of inadequate housing, reduced access to services and poverty. Under these circumstances, Indigenous Australian women suffer a heavy burden of CD and ill-health. Premature mortality due to diabetes, chronic kidney disease (CKD) and cardiovascular disease (CVD) contributes significantly to the gap in life expectancy (LE) for Indigenous women in Australia. Despite the reality of the lived experiences of Indigenous women, positive stories of resilience, strength and outstanding leadership exist throughout the country. These stories are not only remarkable success stories in their own right, they are even more remarkable given that these stories of success and resilience were achieved within a society that had at its structural core, seemingly insurmountable impediments, often present from birth. For example, such impediments saw the author taken home to a tent on the outskirts of town from the hospital following her birth; and until the age of three, she was not counted as a person or citizen of this country. Laws such as the various Aboriginal Protectionist Acts that were in force across Australia from 1838 to the 1970s, reinforced oppression and thwarted the aspirations of many Aboriginal people (Sherwood, 2013). This reality continues to impact on Indigenous people today. As recent as 1980, the author’s own aspirations to become a nurse were seriously eroded by career guidance officers who enthusiastically promoted early school departure and a career as a hospital domestic and cleaner instead of directing her towards further education or a professional career in health. A particularly important focus of this thesis is the research study involving interviews with 72 Australian Indigenous women from four Aboriginal health services in Australia about their roles and responsibilities to their family and community. The author listened to stories of strength, resilience and cohesiveness underpinned by pride and a strong sense of identity and belonging. These women shared how they juggled hectic workplace responsibilities, with having to provide care and support for extended family. This was both a strongly positive factor in their lives, yet the research will also explore the potential impact of their caring roles upon their own health and wellbeing. Methods This study reviewed the published evidence exploring the impact on Indigenous women of living with a CD, and reports on the burden of stress and psychosocial issues for Indigenous women. A systematic review examined intervention programs to address CD and mental health. This review was focused on issues as they affected Indigenous women and highlighted interventions occurring within Aboriginal Medical Services (AMS). Findings from two qualitative research projects are reported. In-depth interviews were undertaken with 21 Indigenous men and women and their healthcare providers as part of the process evaluation accompanying the Kanyini-GAP clinical trial, which aimed to improve health outcomes for people with high cardiovascular risk. In-depth qualitative interviews were also undertaken with 72 Indigenous women from four AMS around Australia to explore their experiences of living with CD and seeking to understand the factors that impacted on their ability to manage their own health. Research findings A review of the literature outlined the historical, social and economic factors that impact on Indigenous women’s health. These social determinants result in a greater incidence and prevalence of CD and premature death. The review also explored the heavy burden of psychosocial stress faced by Indigenous women. A systematic review explored evidence regarding programs addressing CD and mental health or social and emotional wellbeing (SEWB) for Indigenous people. We found a lack of high quality intervention studies, with poor delineation of key outcome measures and indicators of success, and a strong potential for bias in the reporting of results. We were unable to determine the efficacy, cost-effectiveness, or the potential for using programs beyond the original research setting. The in-depth interviews of women from four AMS explored the roles and responsibilities that Indigenous women have in their family and community, and if these roles and responsibilities impacted on the women managing their CD. Women took on significant roles and responsibilities within extended family networks. These responsibilities affected the study participants’ wellbeing and management of their CD was also affected by additional factors such as the incarceration of family members. The heavy burden of CD on the individual, family and wider community was highlighted. The impact of domestic violence is also highlighted, as was the grief related to repeated accounts of death and family members dying. Protective factors that promoted resilience included family support, cultural identity and belonging, education and health service access. The impact upon the author as an Aboriginal woman undertaking this research and the potential for Indigenous researchers to suffer vicarious trauma (VT) through conducting such research is discussed in Chapter 6. Implications of the research The findings presented in this thesis have implications for service delivery, resource allocation and policy development. For Indigenous women to be better able to manage their own health, to support earlier presentation with illness, health maintenance, improved self-management and enhanced quality of life, the extended family and community caring responsibilities of these women need to be taken into account. Better resources to support new mothers, culturally appropriate safe houses for women fleeing family and domestic violence, and flexible models of service delivery to more communities to better accommodate the competing demands placed upon Indigenous women are required to bring about improvements in health and wellbeing